(untitled) (Journal of the College of Basic Education, 2022)
The research problem lies in the merger that we notice among many insiders and workers in the artistic field, and perhaps even at the level of researchers in the history of creative production, as well as decision-makers in religious institutions that sponsor, produce, and incubate religious art, that merger between Eastern Byzantine art and art products Ghouti, which brings them together under the name of Christian art, and in the fact that they represent religious art, of a functional and informative nature that has been harnessed to serve religious institutions. The research gains its importance in being a knowledge addition to the art library that will enrich researchers and scholars in this field and students of art faculties and institutes interested in studying the history of art and icon painting in the Middle Ages in particular. Thus, the aim of the study is to reveal how the religious intellectual structure is represented in the Gothic style.